GREEN SOCIAL WORK AND SUSTAINABLE DEVELOPMENT GOALS: GLOBAL TO LOCAL PERSPECTIVES. - Kumar, Vinay; MA, Suhel (International Journal of Research -GRANTHAALAYAH, 2024)
Green social work is an emerging and futuristic concept within the realm of social work profession. It aims to identify the overlaps between ecological issues and social problems, including poverty, inequity, and social exclusion, in light of a rapidly mounting universal environmental crisis illustrated in climate change, disasters, biodiversity loss and pollution. By promoting social and ecological well-being through sustainable practice and in the spirit of environmental justice, green social work aims to initiate balanced development in the social and ecological well-being of individuals, especially the vulnerable groups who are at the periphery of development. Literature in Green Social Work acknowledges the necessity of contesting this scenario in order to integrate completely ecology within social work practice, policy and advocacy for social justice. This article describes the various approaches of the green social work in practice, including its theoretical roots, methods, challenges, and future implementation for lively and sustainable co-existence of human and the environment. Green social work also is aligned with the United Nations Sustainable Development Goals (SDGs) 13 (Climate Action), 10 (Reduced Inequality), 11 (Sustainable Cities and Communities) and 12 (Responsible Consumption and Production) highlighting its contemporary relevance to society and practice at grassroots to complement the SDGs concerns globally.